Magnetic proximity effect in La0.7Ca0.3MnO3/La0.9Ca0.1MnO3 multilayered film with diffusive interfaces - Prokhorov, V.G.; Kaminsky, G.G.; Lee, Y.P.; Park, S.Y.; Hyun, Y.H.; Park, J.S.; Svetchnikov, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The structural, the magnetic and the transport properties of La0.7Ca0.3MnO3/La0.9Ca0.1MnO3 multilayer film, prepared by rf-magnetron sputtering, have been investigated. The high-resolution electron-microscopy studies reveal the formation of different crystal structures in the constituent sublayers, but without sharp and well-defined interfaces. At the same time, the small regions of double-period modulated phase exist in the La0.9Ca0.1MnO3 sublayers at room temperature, manifesting the formation of charge-ordered antiferromagnetic state. The magnetic measurements reveal a significant enhancement of the ferromagnetic ordering in the La0.9Ca0.1MnO3 layers due to a strong magnetic coupling between the constituent sublayers. The multilayer film shows the anisotropic saturation magnetization at low temperature and the alternating shape of the temperature-dependent anisotropic magnetoresistance near the metal-insulator transition.